Ethical considerations in accident and emergency research. Issue 5 (1st September 2002) - Nee, P A; Griffiths, R D
Abstract : This is the third paper on research in accident and emergency medicine. It discusses the ethical issues in emergency medicine with particular regard to informed consent and the privacy of subjects and patients.